Contexto Sociocultural de la familia y su relación con los Procesos Cognitivos determinantes del Aprendizaje lector inicial en niños y niñas de 5 años de la Institución Educativa Nº 314 del distrito de Rioja en el año 2008 - Grández Noriega, Janina (2009)
The investigation (research) named sociocultural context of the family and his (her, your) relation with the cognitive determinant processes of the reading initial learning in children and 5-year-old girls of the Educational institution N º 314 of the district of Rioja in the year 2008, had for aim (lens) analyze the relation of the sociocultural context of the family with the cognitive determinant processes of the reading initial learning in children and 5-year-old girls of the Educational institution N ° 314 of the district of Rioja in the year 2008. The sociocultural context of the family understands (includes) the level of education of the father and of the mother; the interest of father and of the mother far the education of his (her, your) children; and, the type of family. The cognitive determinant processes of the reading initial learning are: the phonological conscience the semantic recognition and the visual memory (report). The sociocultural context of the family understands (includes) the level of education of the father and of the mother; the interest of father and of the mother far the education of his (her, your) children; and, the type of family. The cognitive determinant processes of the reading initial learning are: the phonological conscience, the semantic recognition and the visual memory (report). Confirmed (Resisted) the hypotheses one has thought that the level of education of the mothers relates inversely proportionally to the cognitive determinant processes of the reading initial learning. The level of education of the parents relates inversely proportionally to the cognitive determinant processes of the reading initial learning. The interest of the mothers for the education of his (her, your) children relates inversely proportionally to the cognitive determinant processes of the reading initial learning. The interest of the parents for the education of his (her, your) children relates inversely proportionally to the cognitive determinant processes of the reading initial learning. The type of family relates inversely proportionally to the cognitive determinant processes of the reading initial learning.